A Novel Clustering Tree-based Video lookup Strategy for Supporting VCR-like Operations in MANETs - Shijie Jia; Ye Guo; Youzhong Ma; Chunlin Kuang; Guofang Kuang (Universitas Ahmad Dahlan, 2017)
Mobile Peer-to-Peer (MP2P) network is a promising avenue for large-scale deployment of Video-on-Demand (VoD) applications over mobile ad-hoc networks (MANETs). In P2P VoD systems, fast search for resources is key determinants for improving the Quality of Service (QoS) due to the low delay of seeking resources caused by streaming interactivity. In this paper, we propose a novel Clustering Tree-based Video Lookup strategy for supporting VCR-like operations in MANETs (CTVL) CTVL selects the chunks with the high popularity as